Cinderella - Scott-Mitchell, Clare (Milsons Point, N.S.W. : Random House, 1999)
Although mistreated by her stepmother and stepsisters, Cinderella meets her prince with the help of her fairy godmother. Main characters are represented as dogs.
Keywords: Fairy tales -- France. Folklore -- France -- Juvenile literature. Fairy tales